Prosecution of Judges and Public Servants - Legal Requirement under Section (197) Cr.P.C. - a Critical Analysis - Upadhyay, R. K. (Indian Forester, 2000)
For prosecution of Judge/Public Servant who is accused of any offence alleged to have been committed by him while acting or purporting to act in discharge of his official duty, sanction of government is mandatory under Sec 197 Cr.P.C. But when public servant is charged of offences related to bribery (Sec 161 I.P.C.), cheating (abetting to cheat), no sanction is required under Sec. 197 Cr.P.C. The objective of giving protection (immunity) to Judges and Public Servants under Sec. 197 Cr.P.C. is to guard against vexatious proceedings against Judge/ Magistrate/Public Servant. The protection given under Sec. 197 Cr.P.C. is not available for Judge/Magistrate/Public Servant, if the act or omission is not connected with official duty.